2020
DOI: 10.3389/fpubh.2020.602334
|View full text |Cite
|
Sign up to set email alerts
|

Cost of Illness, Quality of Life, and Work Outcomes in Active Ankylosing Spondylitis Patients Treated With Adalimumab in China

Abstract: Objectives: To access the cost of illness, quality of life and work limitation in active ankylosing spondylitis (AS) patients using adalimumab in China.Methods: A prospective study was performed in 91 patients with active AS in China. Adult patients (aged ≥ 18 years) fulfilled the 1984 New York modified criteria of AS with the Bath Ankylosing Spondylitis Disease Activity Index ≥ 4 were enrolled. All participants received adalimumab (40 mg per 2 weeks) therapy and completed questionnaires about disease characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
(36 reference statements)
1
5
0
Order By: Relevance
“…Some studies have shown that the reduction of medical costs helps to improve patient compliance [11][12] and reduce the loss of indirect economic costs and the long-term financial burden. 13 We also found that the proportion of patients with psoriasis using biological agents was low (only 1.11% in the research of this study).The proportion of patients using biological agents in the United States is higher than in China. [14][15] High prices affect the use of biological agents.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Some studies have shown that the reduction of medical costs helps to improve patient compliance [11][12] and reduce the loss of indirect economic costs and the long-term financial burden. 13 We also found that the proportion of patients with psoriasis using biological agents was low (only 1.11% in the research of this study).The proportion of patients using biological agents in the United States is higher than in China. [14][15] High prices affect the use of biological agents.…”
Section: Discussionsupporting
confidence: 49%
“…Some studies have shown that the reduction of medical costs helps to improve patient compliance 11-12 and reduce the loss of indirect economic costs and the long-term financial burden. 13…”
Section: Discussionmentioning
confidence: 99%
“…Axial spondyloarthritis (axSpA), a chronic inflammatory disease leading to vertebral and sacroiliac fusion, is characterized by lower back pain and back stiffness in the morning 1–3 . Even though there is still no cure for axSpA patients, the application of tumor necrosis factor‐α (TNF‐α) inhibitor in the treatment of axSpA ameliorates the disease status, including controlling the inflammation, decreasing the disease activity, and improving the health‐related quality of life 4–6 . However, the annual cost of TNF inhibitor is high; in addition, a certain proportion of axSpA patients stop the TNF inhibitor therapy because of the lack of efficacy and the presence of adverse events 7–9 .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Even though there is still no cure for axSpA patients, the application of tumor necrosis factorα (TNFα) inhibitor in the treatment of axSpA ameliorates the disease status, including controlling the inflammation, decreasing the disease activity, and improving the health-related quality of life. [4][5][6] However, the annual cost of TNF inhibitor is high; in addition, a certain proportion of axSpA patients stop the TNF inhibitor therapy because of the lack of efficacy and the presence of adverse events. [7][8][9] Hence, it is essential to find biomarkers to predict the TNF inhibitor response in axSpA patients.…”
Section: Introductionmentioning
confidence: 99%
“…Combined with the keyword outbreak analysis, “inflammation,” “risk” and “improvement” have been the emerging keywords in recent years. This indicates that clinicians are now more focused on the long-term quality of life of patients ( 48 50 ). Through the superimposed visual analysis of keywords, combined with the analysis of highly cited articles displayed in Table 4 and Table 5 in the past 10 years, it can be predicted that “placebo-controlled trial,” “double-blind,” “infliximab,” “improvement,” and other keywords may still break out in the future.…”
Section: Discussionmentioning
confidence: 99%